Bilateral Pleural Effusion as a Rare Manifestation of Snakebite Envenomation: A Case Report - Faria Yunita Utami; Gemilang Khusnurrokhman (Lombok Medical Journal, 2026)
Background: Snakebite envenomation remains a significant global health problem, particularly in tropical regions, with a wide spectrum of clinical manifestations ranging from local tissue injury to life-threatening systemic complications. While coagulopathy, neurotoxicity, and acute kidney injury are commonly reported, pleural effusion is an uncommon manifestation and may indicate severe systemic involvement. Case Presentation : We report a 38-year-old male with grade III snakebite in the right cervical region who developed progressive local swelling, hematoma, and systemic symptoms including dyspnea. The patient experienced radiating pain from the neck to the right upper limb and chest, followed by decreased consciousness and worsening respiratory distress. Physical examination revealed extensive edema involving the neck, chest, and right upper extremity. Dyspnea worsened in the supine position and improved in a semi-upright position, suggesting pleural involvement. Laboratory findings showed leukocytosis and thrombocytopenia, while chest radiography confirmed right-sided pleural effusion with pulmonary infiltrates. Discussion : Pleural effusion in snakebite is rare and is likely caused by increased vascular permeability, systemic inflammatory response, and coagulopathy induced by venom components such as metalloproteinases and phospholipase A2. These mechanisms contribute to capillary leak syndrome and fluid accumulation in the pleural space. Conclusion : Pleural effusion should be considered in patients with severe snakebite presenting with respiratory symptoms. Early recognition and prompt management, including antivenom therapy and supportive care, are essential to prevent clinical deterioration.